SOURCES OF HEALTH INFORMATION IN BRAZIL: a perspective from students of the federal university of Rio de Janeiro - Reddy, Sanhita; Pimenta, Denise Nacif; Kaplan-Liss, Evonne; Guimarães, Maria Cristina Soares (PontodeAcesso, 2014)
In Brazil, health communication and information is an important field, but it has yet to be determined where segments of the population look for health information. This research is a pilot study exploring the use and rating of sources of health information of students at the Federal University of Rio de Janeiro (UFRJ). A survey was administered to students of 18-33 years. The questionnaire was culturally adapted from the Health Information National Trends Survey (HINTS) of the National Cancer Institute-USA. Preference in primary source of health information varied slightly with age; older students depended more on physicians and medical professionals, while younger students used the Internet. While the Internet is the leading primary source of health information for university students, there are still doubts as to its reliability and accuracy. Students tend to use more than one source when finding out information on health, indicating a search process that can be useful for program planners when developing campaigns.